Kreativitas Guru dalam Meningkatkan Kemampuan Berhitung Kelompok B melalui Permainan Congklak - Eny Suprihatin; Merci Padaela (Sekolah Tinggi Teologia Kerusso Indonesia, 2019)
Play and games are an inseparable part of the learning process to develop early childhood skills. Knowledge of arithmetic can be delivered to early childhood, ages 5-6 years, by playing a game. The game is a game of congklak. Congklak is a traditional game that has the benefit of stimulating fine motor skills, and training the child's concentration. Research on Teacher Creativity in Improving Counting Ability of Group B Through the Congklak Game in the Integrated Mahanaim Christian Kindergarten, using the Classroom Action Research methodology. The research model used is the Kurt Lewin model. Four stages are carried out: planning, implementing, observing and reflecting. From the four cycles carried out the results are: of the 20 subjects studied the average achievement value was 6.6. 15 children in the high achievement category, 2 children in the moderate category, and 3 children in the low achievement category. Based on initial observations, it was concluded that there was a significant increase in numeracy skills.